2020
DOI: 10.1002/cplu.202000147
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organogelation Directed by Weak Noncovalent Interactions in Palmitoylated 1,5‐Anhydro‐d‐Glucitol Derivatives

Abstract: We synthesized a series of novel alicyclic compounds by modifying 1,5-anhydro-d-glucitol with two to four palmitoyl chains, and we explored their self-assembly and gelation behaviors in paraffin. The obtained organogels were studied by field emission scanning electron microscopy, atomic force microscopy, variable-temperature Fourier transform IR spectroscopy, X-ray diffraction analysis, polarized optical microscopy, and transmission spectroscopy. While all the palmitoylated derivatives spontaneously formed fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Previously, we reported that 1,5-anhydro-2,3,4,6-tetra- O -palmitoyl- d -glucitol (16AG) shows such temperature dependence. 16AG is a starch-derived, low-molecular-weight organogelator consisting of a palmitoyl chain linked via an ester to the hydroxyl group of 1,5-anhydro- d -glucitol. The solvophobic effect of the aliphatic chain and the weak hydrogen bonding of CH···O allow 16AG molecules to self-assemble into a supramolecular fiber network, which allows 16AG to gelatinize a wide variety of organic solvents, including high-polarity solvents such as alcohols and low-polarity solvents such as liquid paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that 1,5-anhydro-2,3,4,6-tetra- O -palmitoyl- d -glucitol (16AG) shows such temperature dependence. 16AG is a starch-derived, low-molecular-weight organogelator consisting of a palmitoyl chain linked via an ester to the hydroxyl group of 1,5-anhydro- d -glucitol. The solvophobic effect of the aliphatic chain and the weak hydrogen bonding of CH···O allow 16AG molecules to self-assemble into a supramolecular fiber network, which allows 16AG to gelatinize a wide variety of organic solvents, including high-polarity solvents such as alcohols and low-polarity solvents such as liquid paraffin.…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular-mass organogelators can gelate organic solvents at as little as 1 wt % and are used in a variety of fields. We recently determined that C16AG, a fully palmitoylated 1,5-anhydro- d -glucitol, can gelate a variety of organic solvents and investigated its gelation mechanism. , The gelation mechanism was found to be caused by the formation of van der Waals interactions between alkyl chains as well as weak hydrogen bonds between the C–H groups of alkyl chains and the carbonyl groups. Due to these very weak intermolecular interactions, the C16AG gel was fragile to external physical force.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular gels have emerged as fascinating soft materials with tunable physical properties and stimuli-responsive nature. Supramolecular gels with distinct gel–sol transitions have manifested a diverse range of biomedical and material applications. Moreover, the emergence of supramolecular gels has broadened the possibility of wearable materials with the ability to encode information and make complex behaviors easy to be manipulated at the molecular level. , Supramolecular gels are composed of low molecular mass organic gelators (LMOGs). The characteristic of these small molecule gelators is translated via hierarchical self-assembly into nanoscale aggregates. The cooperative effects of preprogrammed noncovalent interactions serve as a driving force to define the direction and dimension of molecular aggregation of LMOGs, promoting the growth of noncovalently associated building blocks through self-assembly. Particularly, the dynamic noncovalent interactions of LMOGs provide a better way of packing through one-dimensional (1D) aggregation and propagate them into elongated fibrillar morphology with a length of several tens of micrometers having unimolecular width, which is a basic requirement for organogel formation. The 1D fibrous structures further intertwine to create three-dimensional (3D) fibrillar networks and a large volume of liquid immobilized therein.…”
Section: Introductionmentioning
confidence: 99%